Social Assistance and Poverty Reduction in Moldova, 2001-2004 : An Impact Evaluation - Verme, Paolo (The World Bank, 2008)
This paper assesses the impact of social assistance benefits on household welfare in Moldova. Ignoring standard issues of impact evaluations such as selection bias, behavioral responses, unobserved heterogeneity and endogeneity, an incidence analysis suggests that increased spending on social assistance enhances the probability of moving out of poverty and reduces the probability of moving into poverty. However, double difference estimates (based on a mimicked randomized experiment) and parametric estimates (based on panel data) indicate that social benefits have not contributed to improve household welfare or reduce poverty. Double difference estimates point to a negative impact on welfare. Parametric estimates do not yield any consistent significant impact on welfare or poverty. The author concludes that the growth in population coverage and expenditure on cash benefits that characterized social assistance policies in recent years has not resulted in a significant improvement in welfare, all other factors being equal